Degradable resin composition, prepreg and copper-clad plate
By developing a degradable resin composition containing bicyclic phenolic resin and bicyclic epoxy resin, the problem of difficult recycling of thermosetting resin materials is solved, and efficient degradation and effective recycling of copper clad material is achieved, and environmental pollution is reduced.
Patent Information
- Application Number
- CN202411975523.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-11
AI Technical Summary
The existing thermosetting resin materials are difficult to recycle and reuse after the end of the use cycle, resulting in waste of resources and environmental pollution. At the same time, the mechanical strength of bio-based thermosetting resins is poor and the glass transition temperature is low, making it difficult to promote and apply in actual production.
A degradable resin composition, including bicyclic phenolic resin and bicyclic epoxy resin, was developed, and a copper clad material with medium Tg level and excellent heat resistance and stability was prepared by reasonably formulating other epoxy resins, curing agents, inorganic fillers and curing accelerators.
It realizes efficient degradation of copper clad material, high degradation efficiency, reduces the generation of electronic waste, and effectively recovers some components, reducing environmental pollution.
Smart Images

Figure SMS_5 
Figure FDA0005220995380000011 
Figure FDA0005220995380000013
Abstract
Description
Technical Field
[0001] The invention relates to the field of copper-clad laminate technology, in particular to a degradable resin composition, a prepreg and a copper-clad laminate. Background Art
[0002] Phenolic resin and epoxy resin are the most widely used thermosetting resins with a long history of development. They are widely used in aerospace, automobile industry, electronics industry, new energy and other fields. This is mainly due to their highly cross-linked network structure after curing. At the same time, the raw materials are simple to prepare and the products produced have excellent performance. In addition, they can be mixed with inorganic fillers or organic fillers to make composite materials, or they can be impregnated with fabrics to make laminated products. However, the raw materials used to prepare these two types of resins currently mainly come from the petrochemical industry, such as common bisphenol A epoxy resin, o-cresol resin, BNE resin, etc., and their synthetic raw materials are all non-renewable resources, which are not in line with the concept of green and sustainable development. In addition, the traditional phenolic resin and epoxy resin have stable structures after curing, making it difficult to simply recycle and reuse their products by physical or chemical means after the end of their use cycle. If they are not handled properly, it will cause environmental pollution. At present, there are mainly the following types of waste for thermosetting resin matrix composite materials: 1. Mechanically grind and crush them into recycled materials of different particle sizes for use as low-value fillers; 2. Convert them into heat energy for recycling through incineration, but the utilization rate is low; 3. Pyrolysis of thermosetting resins under high temperature, high pressure, strong acid, and strong oxidation conditions to achieve the recycling of fiber-reinforced materials. However, the above methods have strict requirements on equipment and operating environment, and will produce secondary pollution, which is not suitable for industrial operation.
[0003] To this end, manufacturers began to use biomass raw materials to prepare degradable phenolic resins or epoxy resins. Among them, vanillin, isosorbide, lignin, starch, eugenol, cardanol, vegetable oil, etc. have been widely used to synthesize bio-based thermosetting phenolic resins or epoxy resins, and show broad application prospects in the fields of coatings, adhesives, composite materials, electronic packaging, etc. Although the above-mentioned bio-based thermosetting phenolic resins and epoxy resins have good degradability, due to the large number of flexible segments contained in biomass raw materials, and the poor mechanical strength and low glass transition temperature of most bio-based epoxy monomer cured products, they are difficult to promote and apply in actual production. As an important field of thermosetting resins, copper clad laminates produce a large amount of scraps and waste every year. At the same time, a large number of copper clad laminates are also present in a large number of discarded electronic product PCBs, resulting in resource waste and environmental pollution. In order to solve this problem, it is urgent to develop a degradable copper clad laminate material. Summary of the invention
[0004] In view of this, the present invention aims to address the deficiencies in the prior art, and its main purpose is to provide a degradable resin composition, a prepreg and a copper clad laminate. The copper clad laminate made from the degradable resin composition not only has excellent degradation performance, but also has excellent heat resistance and stability and reaches a medium Tg level.
[0005] To achieve the above purpose, the present invention adopts the following technical solutions:
[0006] A degradable resin composition, based on 100 parts by weight of organic solids, comprises 25-100 parts of a degradable mixture, 0-75 parts of other epoxy resins, 0-75 parts of a curing agent, 25-45 parts of an inorganic filler, and 0.01-1 parts of a curing accelerator; wherein the degradable mixture is composed of a bicyclic phenol-formaldehyde resin and a bicyclic epoxy resin, the bicyclic phenol-formaldehyde resin is 0-100 parts, the bicyclic epoxy resin is 0-100 parts, when the bicyclic phenol-formaldehyde resin is 0 parts, the amount of the curing agent is not 0, when the bicyclic epoxy resin is 0 parts, the amount of the other epoxy resin is not 0; the structural formula of the bicyclic phenol-formaldehyde resin is as follows:
[0007] 0≤n≤20; R1 is one of hydrogen atom, methyl, ethyl, 2-furyl, phenyl, benzyl, o-hydroxyphenyl, 3,5-dimethoxy-4-hydroxyphenyl; R2 is hydrogen atom;
[0008] The structural formula of the bicyclic epoxy resin is shown below:
[0009] 0≤m≤20; R3 is one of hydrogen atom, methyl, ethyl, 2-furyl, phenyl, benzyl, o-hydroxyphenyl, 3,5-dimethoxy-4-hydroxyphenyl; R4 is glycidyl.
[0010] As a preferred embodiment, the molar ratio of the sum of the reactive groups of the other epoxy resins and the reactive groups of the curing agent to the reactive groups of the degradable mixture is (0-4):1.
[0011] As a preferred embodiment, the molar ratio of the sum of the reactive groups of the curing agent and the reactive groups of the bicyclic phenol-formaldehyde resin to the sum of the epoxy groups of the bicyclic epoxy resin and the epoxy groups of the other epoxy resins is 1:(0.7-1.3).
[0012] As a preferred embodiment, the weight ratio of the inorganic filler to the organic solid is (0.25-0.45):1.
[0013] As a preferred embodiment, the bicyclic phenol-formaldehyde resin is prepared by the following method, the steps of which are as follows:
[0014] (1): salicylaldehyde, erythritol, a first catalyst and a first solvent are added to a three-necked flask, a water separator is set, and the mixture is stirred for a certain period of time under heating and reflux conditions, and after cooling, the mixture is washed with alkali, neutralized and washed with anhydrous ethanol to obtain a diphenol monomer; wherein the molar ratio of the erythritol to the salicylaldehyde is 1:(2-3.5); the first catalyst is p-toluenesulfonic acid, ZrCl4, InCl3, BF3, B 10 H 14 , Bi(OTf)3, Cu(BF4)2·xH2O, DDQ, NBS, pyridinium salt derivatives, imidazolium salt ionic liquids, the amount of the catalyst added is 0.2-1.5% of the mass of erythritol; the first solvent is selected from at least one of DMF, cyclohexane, THF, ether, dioxane, benzene, toluene, the amount of the added solvent is 1-50 times the mass of the erythritol; the heating temperature is 80-140°C; the stirring reaction time is 5-20h;
[0015] (2) adding the diphenol monomer obtained in step (1) to a second solvent, adding an appropriate amount of a second catalyst, removing air from the reaction system with nitrogen and raising the temperature to 60-100° C., slowly dropping a measured amount of aldehyde compound into the reaction system using a constant pressure dropping funnel to carry out an addition polycondensation reaction, raising the temperature to 100-140° C. after the dropwise addition is complete, continuing the reaction for 2 hours, neutralizing, filtering, washing, desolvating under reduced pressure and removing unreacted diphenol monomer, to obtain a bicyclic phenol-formaldehyde resin; wherein the second solvent is water, ethanol, propylene glycol, or a mixture of the following: The invention relates to a method for preparing the present invention wherein the present invention comprises: preparing a catalytic converter comprising: a catalyst comprising at least one of ketone, butanone, and methyl isobutyl ketone; the second catalyst is at least one of barium hydroxide, sodium hydroxide, magnesium hydroxide, ammonia water, and triethylamine, and the addition amount accounts for 0.5-10%% of the mass of the diphenol monomer; the aldehyde compound is at least one of formaldehyde, acetaldehyde, propionaldehyde, paraformaldehyde, paraldehyde, furfural, benzaldehyde, phenylacetaldehyde, and salicylaldehyde, the ratio of the addition amount of aldehyde group of the aldehyde compound to the addition amount of phenolic hydroxyl group is (1.1-2.5):1, and the dripping time of the aldehyde compound is 10-120min.
[0016] As a preferred embodiment, the bicyclic epoxy resin is prepared by the following method, the steps of which are as follows:
[0017] (1) The bicyclic phenol-formaldehyde resin obtained above is mixed with epichlorohydrin and a phase transfer agent in a three-necked flask, and the temperature is raised to 40-100° C. and maintained for 2 hours for etherification, and then the temperature is maintained at 70° C. and a NaOH solution is slowly added dropwise, and the reaction is continued for 3 hours, and a bicyclic epoxy resin is obtained by liquid separation, water washing, and reduced pressure distillation; wherein the phase transfer agent is at least one of isopropyl alcohol and tetrabutylammonium bromide, and the mass ratio of the bicyclic phenol-formaldehyde resin to the epichlorohydrin is (1.4-2.1):1.
[0018] As a preferred embodiment, the other epoxy resins are at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, biphenyl epoxy resin, isocyanate modified epoxy resin, o-cresol epoxy resin, naphthalene epoxy resin, alicyclic epoxy resin, brominated epoxy resin, resorcinol epoxy resin, polyethylene glycol epoxy resin, trifunctional epoxy resin, tetrafunctional epoxy resin, dicyclopentadiene epoxy resin, and phenolic epoxy resin; the curing agent is at least one of phenolic curing agent, fatty amine curing agent, aromatic amine curing agent, and heterocyclic amine.
[0019] As a preferred embodiment, the inorganic filler is at least one of aluminum hydroxide, boehmite, silicon dioxide, modified silicon dioxide, talc, mica, barium sulfate, lithopone, calcium carbonate, wollastonite, kaolin, brucite, diatomaceous earth, bentonite, and pumice powder; the curing accelerator is at least one of 2-methylimidazole, 1-methylimidazole, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-undecylimidazole, 2-phenyl-4-methylimidazole, tetramethylammonium bromide, lithium n-butoxide, aluminum chloride complex, quaternary ammonium salt polymer, 2,4,6-tris(dimethylaminomethyl)phenol, 1-allyl-3-methylimidazole chloride, and 1-ethyl-3-methylimidazole acetate.
[0020] A semi-cured sheet is prepared from the aforementioned degradable resin composition, and its preparation method is as follows: the aforementioned degradable resin composition is dissolved and dispersed in an appropriate amount of solvent, and stirred and dispersed evenly to obtain a glue solution, then, the glue solution is impregnated on a fiber-reinforced material, and then, after drying in a ventilated place, it is placed at 100-250°C and baked for 1-15 minutes to obtain the semi-cured sheet.
[0021] A copper clad laminate is prepared from the aforementioned prepreg, and its preparation method is as follows:
[0022] The aforementioned semi-cured sheets are stacked in the form of at least one sheet, and after stacking, one or both sides are covered with copper foil for assembly, and after assembly, a copper clad laminate is prepared by hot pressing in a hot press, the curing temperature is 150-250° C., the curing pressure is 200-400 psi, and the curing time is 60-120 min, so as to obtain the copper clad laminate.
[0023] Compared with the prior art, the present invention has obvious advantages and beneficial effects. Specifically, it can be seen from the above technical solution that:
[0024] Each repeating unit of the bicyclic phenolic resin and the bicyclic epoxy resin in the present invention application contains a degradable bicyclic diacetal structure and a reactive hydroxyl group or epoxy group, so that the resin composition has a curing property, and the content of the degradable structure in the cured product after curing is very high; at the same time, the presence of the hydroxyl group and the epoxy group enables the degradable mixture to be used in combination with the other epoxy resins and the curing agent, and the Tg, heat resistance and other properties of the resin composition are improved by the curing agent and the other epoxy resins. Because the degradable structure content of the degradable mixture is high, even if the degradable structure content in the resin system is reduced after being combined with the other epoxy resins, the cured resin can still maintain a high degradability, and also obtains higher Tg and good heat resistance; and the bicyclic diacetal structure has excellent heat stability and mechanical properties, and is sensitive to acid. The present invention introduces the bicyclic diacetal structure into the resin system to prepare a phenolic resin or epoxy resin containing the bicyclic diacetal structure, which not only gives the resin composition and the resin product excellent heat stability and mechanical strength, but also makes the resin composition and the copper clad laminate prepared using the resin composition have excellent performance during the service life. At the same time, after the end of the service life, it can be degraded under acidic conditions, with high degradation efficiency, little pollution to the environment, and convenient and safe, reducing the generation of electronic waste, and realizing effective recovery of some components.
[0025] In order to more clearly illustrate the structural features and effects of the present invention, the present invention is described in detail below in conjunction with specific embodiments. DETAILED DESCRIPTION
[0026] The present invention discloses a degradable resin composition, which comprises 25-100 parts of a degradable mixture, 0-75 parts of other epoxy resins, 0-75 parts of a curing agent, 25-45 parts of an inorganic filler, and 0.01-1 parts of a curing accelerator, based on 100 parts by weight of organic solids; wherein the degradable mixture is composed of a bicyclic phenol-formaldehyde resin and a bicyclic epoxy resin, wherein the bicyclic phenol-formaldehyde resin is 0-100 parts, and the bicyclic epoxy resin is 0-100 parts; it should be noted that, because the bicyclic phenol-formaldehyde resin has a curing effect, it can act as a curing agent in a resin system, therefore, when the bicyclic phenol-formaldehyde resin is not 0 parts, the amount of the curing agent can be 0, and when the bicyclic phenol-formaldehyde resin is 0 parts, the amount of the curing agent shall not be 0; when the bicyclic epoxy resin is 0 parts, the amount of the other epoxy resin is not 0; the structural formula of the bicyclic phenol-formaldehyde resin is as follows:
[0027] 0≤n≤20; R1 is one of hydrogen atom, methyl, ethyl, 2-furyl, phenyl, benzyl, o-hydroxyphenyl, 3,5-dimethoxy-4-hydroxyphenyl; R2 is hydrogen atom;
[0028] The structural formula of the bicyclic epoxy resin is shown below:
[0029] 0≤m≤20; R3 is one of hydrogen atom, methyl, ethyl, 2-furyl, phenyl, benzyl, o-hydroxyphenyl, 3,5-dimethoxy-4-hydroxyphenyl; R4 is glycidyl.
[0030] Specifically, the molar ratio of the sum of the reactive groups of the other epoxy resins and the reactive groups of the curing agent to the reactive groups of the degradable mixture is (0-4):1; the molar ratio of the sum of the reactive equivalents of the curing agent and the reactive equivalents of the bicyclic phenol-formaldehyde resin to the sum of the epoxy equivalents of the bicyclic epoxy resin and the epoxy equivalents of the other epoxy resins is 1:(0.7-1.3); the weight ratio of the inorganic filler to the organic solid is (0.25-0.45):1; the other epoxy resins are bisphenol A epoxy resin, bisphenol F epoxy resin, biphenyl epoxy resin, isocyanate modified epoxy resin, o-cresol epoxy resin, naphthalene epoxy resin, alicyclic epoxy resin, brominated epoxy resin, resorcinol epoxy resin, polyethylene glycol epoxy resin, trifunctional epoxy resin, tetrafunctional epoxy resin, dicyclopentadiene epoxy resin, phenol At least one of aldehyde type epoxy resins; the curing agent is at least one of phenolic curing agent, fatty amine curing agent, aromatic amine curing agent, and heterocyclic amine; the inorganic filler is at least one of aluminum hydroxide, boehmite, silicon dioxide, modified silicon dioxide, talc, mica, barium sulfate, lithopone, calcium carbonate, wollastonite, kaolin, brucite, diatomaceous earth, bentonite, and pumice powder; the curing accelerator is at least one of 2-methylimidazole, 1-methylimidazole, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-undecylimidazole, 2-phenyl-4-methylimidazole, tetramethylammonium bromide, lithium n-butoxide, aluminum chloride complex, quaternary ammonium salt polymer, 2,4,6-tris(dimethylaminomethyl)phenol, 1-allyl-3-methylimidazole chloride, and 1-ethyl-3-methylimidazole acetate.
[0031] In addition, the bicyclic phenol-formaldehyde resin is prepared by the following method, the steps of which are as follows:
[0032] (1): salicylaldehyde, erythritol, a first catalyst and a first solvent are added together into a three-necked flask, a water separator is set, and the mixture is stirred for a certain period of time under heating and reflux conditions, and after cooling, the mixture is washed with alkali, neutralized and washed with anhydrous ethanol to obtain a diphenol monomer; wherein the molar ratio of the erythritol to the salicylaldehyde is 1:(2-3.5), preferably 1:(2.2-2.6); the first catalyst is p-toluenesulfonic acid, ZrCl4, InCl3, BF3, B 10 H 14, Bi(OTf)3, Cu(BF4)2·xH2O, DDQ, NBS, pyridinium salt derivatives, imidazolium salt ionic liquids, the amount of the catalyst added is 0.2-1.5% of the mass of erythritol, preferably 0.5-1%; the first solvent is selected from at least one of DMF, cyclohexane, THF, ether, dioxane, benzene, toluene, preferably DMF and methyl isobutyl ketone, the amount of the added amount is 1-50 times the mass of erythritol, preferably 10-30 times; the heating temperature is 80-140°C, preferably 90-110°C; The stirring reaction time is 5-20h, preferably 8-15h; it should be noted that salicylaldehyde is a bio-based aromatic aldehyde and naturally exists in essential oils such as Chinese cinnamon oil and marigold oil; erythritol is widely present in fungi, mushrooms, lichens, eye lenses, plasma, fetal fluid and other plants and animals, and can also be produced by fermentation of glucose. Both are renewable raw materials, while the resins currently used in the copper clad laminate industry mainly come from the petrochemical industry and are non-renewable. The main raw materials for the synthesis of the bicyclic phenolic resin applied in the present invention are salicylaldehyde and erythritol, so that the use of the degradable resin composition applied in the present invention can reduce carbon emissions.
[0033] (2) adding the diphenol monomer obtained in step (1) to a second solvent, adding an appropriate amount of a second catalyst, removing air from the reaction system with nitrogen and raising the temperature to 60-100° C., preferably 70-90° C., slowly dropping a measured amount of aldehyde compound into the reaction system using a constant pressure dropping funnel to carry out an addition polycondensation reaction, raising the temperature to 100-140° C., preferably 10-130° C. after the dropwise addition is complete, continuing the reaction for several hours, neutralizing, filtering, washing, desolvating under reduced pressure and removing unreacted diphenol monomer, to obtain a bicyclic phenol-formaldehyde resin; wherein the second solvent is water, ethanol, acetone, butanone, or toluene. The second catalyst is at least one of barium hydroxide, sodium hydroxide, magnesium hydroxide, ammonia water and triethylamine, and the addition amount accounts for 0.5-10% of the mass of the diphenol monomer, preferably 1-3%; the aldehyde compound is at least one of formaldehyde, acetaldehyde, propionaldehyde, paraformaldehyde, paraldehyde, furfural, benzaldehyde, phenylacetaldehyde and salicylaldehyde, the ratio of the addition amount of aldehyde group of the aldehyde compound to the addition amount of phenolic hydroxyl group is (1.1-2.5):1, preferably (1.2-1.6):1, and the dripping time of the aldehyde compound is 10-120min, preferably 20-40min.
[0034] The bicyclic epoxy resin is prepared by the following method, the steps of which are as follows:
[0035] (1) The bicyclic phenol-formaldehyde resin obtained above is mixed with epichlorohydrin and a phase transfer agent in a three-necked flask, and the temperature is raised to 40-100° C. and maintained for several hours for etherification, and then the temperature is maintained at 70° C. and a NaOH solution is slowly added dropwise, and the reaction is continued for several hours to obtain a bicyclic epoxy resin by liquid separation, water washing, and reduced pressure distillation; wherein the phase transfer agent is at least one of isopropyl alcohol and tetrabutylammonium bromide, and the mass ratio of the bicyclic phenol-formaldehyde resin to the epichlorohydrin is (1.4-2.1):1.
[0036] The present invention also discloses a semi-cured sheet, which is made from the aforementioned degradable resin composition. The preparation method thereof is as follows: the aforementioned degradable resin composition is dissolved and dispersed in an appropriate amount of solvent, and stirred and dispersed evenly to obtain a glue solution, then, the glue solution is impregnated on a fiber-reinforced material, and then, after drying in a ventilated place, placed at 100-250°C and baked for 1-15 minutes to obtain the semi-cured sheet.
[0037] The present invention also discloses a copper clad laminate, which is made from the aforementioned prepreg, and the preparation method thereof is as follows:
[0038] The aforementioned semi-cured sheets are stacked in the form of at least one sheet, and after stacking, one or both sides are covered with copper foil for assembly, and after assembly, a copper clad laminate is prepared by hot pressing in a hot press, the curing temperature is 150-250° C., the curing pressure is 200-400 psi, and the curing time is 60-120 min, so as to obtain the copper clad laminate.
[0039] The above copper clad laminate degradation and recycling method has the following specific steps:
[0040] (1) etching the copper-clad laminate through an etching line to obtain a copper ion recovery solution and a core plate;
[0041] (2) placing the core plate obtained in step (1) in a slightly acidic solution, and decomposing the cured resin composition by soaking, stirring and heating to obtain glass fiber cloth, filler and decomposition product solution. The slightly acidic solution can be an acidic organic solution or an acidic aqueous solution. The degradation temperature is 50-120°C and the degradation time is 0.5-6h. The obtained glass cloth can be washed and reused, and the filler can be recovered by filtration or centrifugation.
[0042] (3) The decomposed product solution obtained in step (2) can be subjected to alkali precipitation, neutralization, centrifugation, distillation, etc. to obtain a degraded resin, which can be reused.
[0043] The degradable resin composition described in the present invention will form a three-dimensional polymer network after curing. The three-dimensional polymer network contains a bicyclic diacetal structure. The bicyclic diacetal structure can be hydrolyzed under acidic conditions, thereby breaking to obtain short-chain resin and linear resin, thereby achieving the purpose of degradation and recovery. The degradation performance tests of the subsequent multiple embodiments and comparative examples are all tested under the same conditions using this method.
[0044] The following is a detailed description in conjunction with a plurality of embodiments and comparative examples. The specific components are selected as follows, and the proportions of the components are shown in Table 1.
[0045] Degradable mixture: bicyclic phenolic resin (homemade), bicyclic epoxy resin (homemade);
[0046] Other epoxy resins: BPA epoxy resin, produced by Shengquan Group, model SQAN203, epoxy equivalent of 220g / eq;
[0047] Curing agent: BPA type phenolic resin, produced by Shengquan Group, model SH-2120, hydroxyl equivalent of 120g / eq, 4,4'-diaminodiphenyl sulfone, model DDS, hydroxyl equivalent of 62g / eq;
[0048] Inorganic filler: silica powder;
[0049] Curing accelerator: 2-methylimidazole;
[0050] Solvent: butanone.
[0051] The bicyclic phenol-formaldehyde resins of the following embodiments are prepared by the following method, wherein the steps are as follows:
[0052] (1) 26.9 g of salicylaldehyde, 12.2 g of erythritol, 0.1 g of p-toluenesulfonic acid and 250 ml of DMF were added to a three-necked flask, a water separator was set and the mixture was stirred and reacted at 100° C. for 10 h. After cooling, the mixture was washed with a 5% sodium bicarbonate aqueous solution, neutralized with a weak acid and washed with anhydrous ethanol to obtain a diphenol monomer containing a bicyclic diacetal structure, with a yield of 73%;
[0053] (2): 29 g of the diphenol monomer obtained in step (1) was added to 200 ml of methyl isobutyl ketone, and 0.4 g of p-toluenesulfonic acid was added at the same time. The air in the reaction system was purged with nitrogen and the temperature was raised to 90° C. 10 g wt % formaldehyde aqueous solution was slowly added dropwise to the reaction system using a constant pressure dropping funnel to carry out an addition polycondensation reaction. After the addition was completed, the temperature was raised to 120° C. and the reaction was continued for 2 h. After washing with water, desolventizing and removing the unreacted diphenol monomer, the bicyclic phenol-formaldehyde resin was obtained, and its Mn was 1620 g / mol and its hydroxyl equivalent was 180 g / eq.
[0054] The bicyclic epoxy resins of the following embodiments are prepared by the following method, wherein the steps are as follows:
[0055] (1) 20 g of the bicyclic phenol-formaldehyde resin prepared by the above method, 12 g of epichlorohydrin and 100 ml of a phase transfer agent are added to a three-necked flask, wherein the phase transfer agent is isopropyl alcohol. The temperature is raised to 85° C. and maintained for 2 h for etherification. Then, the temperature is maintained at 70° C. and a 20 wt % NaOH solution is slowly added dropwise to the four-necked flask using a constant pressure dropping funnel. The addition time is controlled to be 1 h. Then, the reaction is continued for 3 h, and the salt generated at the bottom of the flask is removed by siphoning. A 20 wt % NaOH solution is added and the reaction is continued for 1 h. Unreacted epichlorohydrin and isopropyl alcohol are removed by washing with water and reducing pressure to obtain the bicyclic epoxy resin having an epoxy equivalent of 220 g / eq.
[0056]
[0057] Table 1
[0058] Preparation of copper-clad laminates of the above-mentioned multiple embodiments and comparative examples: First, the above-mentioned components are added to butanone in the amounts indicated in Table 1 for mixing to obtain a uniformly dispersed glue solution. The butanone not only serves as a solvent but also controls the total solid content of the glue solution, so that the glue reaches a suitable viscosity for the subsequent preparation of a prepreg; then, 2116 glass fiber cloths are respectively immersed in the above-mentioned glue solution for gluing, and baked in an oven at 183°C for 3 minutes to obtain a prepreg, and a prepreg of 2116 specifications is obtained, and the glue content of the prepreg of 2116 specifications is controlled at 58%; then, 6 pieces of the above-mentioned 2116 specifications of the prepreg are stacked, and a piece of Hoz copper foil is provided on the upper and lower sides, and pressed in a vacuum press according to a predetermined procedure, and hot pressed for 90 minutes at a temperature of 190°C and a pressure of 350psi to prepare a copper-clad laminate with a thickness of 0.8 mm; the physical property test of the copper-clad laminate is also taken from this specification. In addition, the degradation process mainly occurs at the interface between the material and the degradation liquid, and proceeds gradually from the outside to the inside. In order to facilitate the comparison of the degradation ability of the copper clad laminate, a copper clad laminate with a specification of 7628*2 was taken for degradation ability test, and its preparation process was consistent with that of the physical property board.
[0059] The copper clad laminates prepared in the above-mentioned embodiments and comparative examples were subjected to performance tests, and the test results are shown in Table 2. The test method is as follows:
[0060] Tg: GBT 19466.2-2004;
[0061] Tin floating: Use a sampling machine to take 3 copper-clad boards with a size of 50*50mm. After treating the edge burrs with 800-mesh sandpaper, place them in an oven at 105-120°C for 2h to dry. Subsequently, place the test samples on the tin water at 288°C and observe the explosion time within 300s. Take the average value of the 3 samples and record the data;
[0062] Water absorption rate: IPC-TM-650 2.6.2.1;
[0063] Degradability evaluation of copper-clad laminates: First, etch the copper on the surface of the copper-clad laminate with a specification of 7628*2 to obtain the core board. Use a sampling machine to take 5 samples of 15*15mm on the core board. After polishing the edges smoothly, wash them and place them in an oven at 105°C for 3h. Take out and record the total mass W1. Subsequently, place the 5 samples in an aqueous solution of 0.3mol / L HCl with a solid-liquid ratio of 1:100. Stir at 80°C at a speed of 300rpm for 3h to carry out degradation. After completion, cool and take out all the solids with fiberglass cloth and rinse and dry them. Observe the degradation situation of the core board and record the degradation mass W2; and use the following formula to evaluate the degradation degree D(%) of the prepared copper-clad laminate and conduct grading:
[0064] D = [1 - (W2 - 0.461) / (W1 - 0.461)] * 100%;
[0065] Among them, 0.461 is the total mass g of the fiberglass cloth contained in the 5 test samples obtained by calculation.
[0066] If D ≤ 10%, it is recorded as ╳, indicating poor degradation ability; if 10% < D ≤ 50%, it is recorded as ☉, indicating general degradation ability. At this time, the inner layer glue of the sample generally has not started to degrade; if 50% < D ≤ 80%, it is recorded as ☉☉, indicating good degradation ability. At this time, a part of the inner layer glue has degraded; if D > 80%, it is recorded as ☉☉☉, indicating excellent degradation ability. At this time, all the glue has been basically completely degraded.
[0067] Tg / ℃ Float tin / s Water absorption / % Degradation degree (3h) Degradation degree (8h) Example 1 148 250 0.11 ☉☉☉ ☉☉☉ Example 2 161 >300 0.11 ☉☉☉ ☉☉☉ Example 3 164 >300 0.15 ☉☉ ☉☉ Example 4 140 270 0.11 ☉☉☉ ☉☉☉ Example 5 159 >300 0.11 ☉☉☉ ☉☉☉ Example 6 153 >300 0.10 ☉☉ ☉☉ Example 7 139 160 0.12 ☉☉☉ ☉☉☉ Example 8 178 >300 0.12 ☉☉ ☉☉☉ Example 9 162 >300 0.10 ☉☉ ☉☉☉ Example 10 156 >300 0.11 ☉☉☉ ☉☉☉ Comparative Example 1 169 >300 0.11 ╳ ╳ Comparative Example 2 183 >300 0.09 ╳ ╳
[0068] Table 2
[0069] The above data are analyzed. It can be clearly seen from Examples 1-10 and Comparative Examples 1-2 that the introduction of bicyclic phenolic resin and bicyclic epoxy resin into the resin system not only has excellent heat resistance and stability, but also Tg can reach the medium Tg level. More importantly, the degradation performance is excellent, while the degradation performance of Comparative Examples 1-2 is extremely poor, and after being discarded, it cannot be effectively degraded, thereby causing waste of resources and environmental pollution; and it can be seen from Example 7 that the resin system only adopts the bicyclic phenolic resin and bicyclic epoxy resin prepared by the present invention, and the degradation degree of the prepared copper clad laminate reaches ☉☉☉, but it is relatively poor in Tg, heat resistance and stability. Although it can be used in the subsequent preparation of printed circuit boards, due to its low Tg, the subsequent preparation The performance of the printed circuit board cannot reach a better level; further, on the basis of Example 7, the bicyclic phenolic resin or the bicyclic epoxy resin is completely replaced by other epoxy resins or curing agents with corresponding functions, and the corresponding function refers to the role of providing active hydrogen or epoxy groups during the curing process, which is equivalent to Example 1 and Example 4, and the degradation performance is still ☉☉☉, and Tg can also reach the level of 148°C; further, on the basis of Example 1 and Example 4, 30% of the bicyclic phenolic resin or the bicyclic epoxy resin is replaced by other epoxy resins or curing agents with corresponding functions, which is equivalent to Example 2 and Example 5. If 50% of the bicyclic phenolic resin or the bicyclic epoxy resin is replaced by the corresponding Other epoxy resins or curing agents with the same function, that is, equivalent to Example 3 and Example 6, it can be clearly seen that after replacement, the proportion of the bicyclic phenolic resin and the bicyclic epoxy resin in the resin system decreases, that is, the content of the bicyclic diacetal structure in the resin system decreases, so that the copper clad laminates prepared in Example 2, Example 3, Example 5, and Example 6 are all greater than 300s in heat resistance, and Tg increases with the increase in the amount of replacement. However, compared with Example 2 and Example 5, the degradation rates of Example 3 and Example 6 are reduced. After 8 hours of degradation, the degradation degrees of Example 3 and Example 6 are only ☉☉. This is because the proportion of the degradable mixture in these two embodiments is very low, so that after curing The bicyclic diacetal structure in the cross-linked network is very small, which will result in that although the bicyclic diacetal structure has been completely broken, the cross-linking site still exists, so that the three-dimensional cross-linking structure is still maintained, showing a state that cannot be completely degraded. In order to ensure that the copper clad laminate can be degraded faster and as much as possible, the proportion of the degradable mixture in the resin system should be greater than 50%; In addition, Example 4 and Example 8 respectively use DDS and SH-2120 as curing agents. It can be found that both have good heat stability, and the Tg of the example cured with DDS is significantly higher, close to 180°C, but the degradation efficiency is slightly poor, and it is only ☉☉ after degradation for 3 hours, indicating that the cross-linking density can be increased by using a low equivalent resin, thereby increasing Tg;By reducing the proportion of DDS in the resin system, see Examples 9 and 10 for details, it is found that Example 10, in which the amount of DDS added is reduced to nearly half of Example 8, can achieve a degradation degree of ☉☉☉ after 3 hours of degradation, while Examples 8 and 9 need to degrade for 8 hours. This is because the resin compositions of Examples 8 and 9 have a higher crosslinking density, and their high crosslinking density reduces the degradation rate; Based on the above discussion, it can be seen that if the resin composition only contains bicyclic phenolic resin and bicyclic epoxy resin, the obtained copper clad laminate can be degraded, but the heat resistance is poor; using bicyclic phenolic resin alone with other epoxy resins or using bicyclic epoxy resin alone with curing agent can achieve better degradation ability while taking into account better heat resistance stability; and, using bicyclic phenolic resin, bicyclic epoxy resin with other epoxy resins and curing agent together can improve other aspects of the performance of the copper clad laminate, such as increasing Tg, reducing water absorption and improving heat resistance, but adding too much other epoxy resins and curing agents will lead to reduced degradability. ;
[0070] The above description is only a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any slight modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A degradable resin composition, characterized in that: Based on 100 parts by weight of organic solids, the composition comprises 25-100 parts of a degradable mixture, 0-75 parts of other epoxy resins, 0-75 parts of a curing agent, 25-45 parts of an inorganic filler, and 0.01-1 parts of a curing accelerator; wherein the degradable mixture is composed of a bicyclic phenol-formaldehyde resin and a bicyclic epoxy resin, wherein the bicyclic phenol-formaldehyde resin is 0-100 parts, and the bicyclic epoxy resin is 0-100 parts. When the bicyclic phenol-formaldehyde resin is 0 parts, the amount of the curing agent is not 0, and when the bicyclic epoxy resin is 0 parts, the amount of the other epoxy resin is not 0. The structural formula of the bicyclic phenol-formaldehyde resin is as follows: One of methyl, ethyl, 2-furyl, phenyl, benzyl, o-hydroxyphenyl, and 3,5-dimethoxy-4-hydroxyphenyl; R2 is a hydrogen atom; The structural formula of the bicyclic epoxy resin is shown below: R3 is one of a hydrogen atom, a methyl group, an ethyl group, a 2-furyl group, a phenyl group, a benzyl group, an o-hydroxyphenyl group, and a 3,5-dimethoxy-4-hydroxyphenyl group; and R4 is a glycidyl group.
2. The degradable resin composition according to claim 1, characterized in that: The molar ratio of the sum of the reactive groups of the other epoxy resins and the reactive groups of the curing agent to the reactive groups of the degradable mixture is (0-4):
1.
3. The degradable resin composition according to claim 1, characterized in that: The molar ratio of the sum of the reactive groups of the curing agent and the reactive groups of the bicyclic phenol-formaldehyde resin to the sum of the epoxy groups of the bicyclic epoxy resin and the epoxy groups of the other epoxy resins is 1:(0.7-1.3).
4. The degradable resin composition according to claim 1, characterized in that: The weight ratio of the inorganic filler to the organic solid is (0.25-0.45):
1.
5. The degradable resin composition according to claim 1, characterized in that: The bicyclic phenol-formaldehyde resin is prepared by the following method, and the steps are as follows: (1): salicylaldehyde, erythritol, a first catalyst and a first solvent are added to a three-necked flask, a water separator is set, and the mixture is stirred for 5-20 hours under reflux at a temperature of 80-140° C., and after cooling, alkali washing, neutralization and anhydrous ethanol washing are performed to obtain a diphenol monomer; wherein the molar ratio of the erythritol to the salicylaldehyde is 1:(2-3.5); the first catalyst is p-toluenesulfonic acid, ZrCl4, InCl3, BF3, B 10 H 14 , Bi(OTf)3, Cu(BF4)2·xH2O, DDQ, NBS, pyridinium salt derivatives, imidazolium salt ionic liquids, the amount of the catalyst added is 0.2-1.5% of the mass of the erythritol; the first solvent is selected from at least one of DMF, cyclohexane, THF, ether, dioxane, benzene, toluene, the amount of the first solvent added is 1-50 times the mass of the erythritol; (2) adding the diphenol monomer obtained in step (1) to a second solvent, adding an appropriate amount of a second catalyst, removing air from the reaction system with nitrogen and raising the temperature to 60-100° C., slowly dropping a measured amount of aldehyde compound into the reaction system using a constant pressure dropping funnel to carry out an addition polycondensation reaction, raising the temperature to 100-140° C. after the dropwise addition is complete, continuing the reaction for 2 hours, neutralizing, filtering, washing, desolvating under reduced pressure and removing unreacted diphenol monomer, to obtain a bicyclic phenol-formaldehyde resin; wherein the second solvent is water, ethanol, acetone, butane The invention relates to a method for preparing the present invention wherein the present invention comprises the following steps: the step of: preparing the present invention comprises the following steps: the step of preparing the present invention comprises the following steps: the step of preparing the present invention comprises the following steps: the step of preparing the present invention comprises the following steps: the step of preparing the present invention comprises the following steps: the step of preparing the present invention comprises the following steps: the step of preparing the present invention comprises the following steps:
6. The degradable resin composition according to claim 5, characterized in that: The bicyclic epoxy resin is prepared by the following method, the steps of which are as follows: (1) The bicyclic phenol-formaldehyde resin obtained above is mixed with epichlorohydrin and a phase transfer agent in a three-necked flask, and the temperature is raised to 40-100° C. and maintained for 2 hours for etherification, and then the temperature is maintained at 70° C. and a NaOH solution is slowly added dropwise, and the reaction is continued for 3 hours, and a bicyclic epoxy resin is obtained by liquid separation, water washing, and reduced pressure distillation; wherein the phase transfer agent is at least one of isopropyl alcohol and tetrabutylammonium bromide, and the mass ratio of the bicyclic phenol-formaldehyde resin to the epichlorohydrin is (1.4-2.1):
1.
7. The degradable resin composition according to claim 1, characterized in that: The other epoxy resins are at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, biphenyl epoxy resin, isocyanate modified epoxy resin, o-cresol epoxy resin, naphthalene epoxy resin, alicyclic epoxy resin, brominated epoxy resin, resorcinol epoxy resin, polyethylene glycol epoxy resin, trifunctional epoxy resin, tetrafunctional epoxy resin, dicyclopentadiene epoxy resin, and phenolic epoxy resin; the curing agent is at least one of phenolic curing agent, fatty amine curing agent, aromatic amine curing agent, and heterocyclic amine.
8. The degradable resin composition according to claim 1, characterized in that: The inorganic filler is at least one of aluminum hydroxide, boehmite, silicon dioxide, modified silicon dioxide, talc, mica, barium sulfate, lithopone, calcium carbonate, wollastonite, kaolin, brucite, diatomaceous earth, bentonite, and pumice powder; the curing accelerator is at least one of 2-methylimidazole, 1-methylimidazole, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-undecylimidazole, 2-phenyl-4-methylimidazole, tetramethylammonium bromide, lithium n-butoxide, aluminum chloride complex, quaternary ammonium salt polymer, 2,4,6-tris(dimethylaminomethyl)phenol, 1-allyl-3-methylimidazole chloride, and 1-ethyl-3-methylimidazole acetate.
9. A prepreg, characterized in that: The semi-cured sheet is prepared from the degradable resin composition as described in any one of claims 1 to 8, and the preparation method is as follows: dissolving and dispersing the degradable resin composition as described in any one of claims 1 to 8 in an appropriate amount of solvent, and stirring and dispersing it evenly to obtain a glue solution, then impregnating the glue solution on a fiber-reinforced material, and then drying it in a ventilated place, placing it at 100-250°C, and baking it for 1-15 minutes to obtain the semi-cured sheet.
10. A copper clad laminate, characterized in that: The prepreg as claimed in claim 9 is prepared by the following method: The semi-cured sheets as described in claim 9 are stacked in the form of at least one sheet, and after stacking, one or both sides are covered with copper foil for assembly, and after assembly, a copper clad laminate is prepared by hot pressing in a hot press, the curing temperature is 150-250° C., the curing pressure is 200-400 psi, and the curing time is 60-120 min to obtain the copper clad laminate.